Double-layer microporous structure of gas diffusion layer and preparation method of double-layer microporous structure
By designing the double-layer microporous structure of the gas diffusion layer of the fuel cell and combining the design of hydrophobic and hydrophilic microporous layers, the problem of difficulty in taking into account water management and free radical capture functions in the prior art is solved, and efficient water management and metals are achieved Ion capture improves the performance and life of fuel cells.
Patent Information
- Application Number
- CN202411573438.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing fuel cell gas diffusion layer is difficult to take into account the efficient water management and radical capture functions, and is costly, which affects the pore structure and production costs.
Design a gas diffusion layer bilayer microporous structure, including a hydrophobic microporous layer and a hydrophilic microporous layer, to achieve efficient water management and metal ion capture functions through specific slurry formulation and preparation processes.
It realizes excellent drainage capacity and performance improvement of fuel cells during large-electrical tight operation, while reducing metal ion pollution and improving the operating life and performance stability of the stack.
Smart Images

Figure CN119481094A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells and relates to a double-layer microporous structure of a gas diffusion layer and a preparation method thereof. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC) is a clean and efficient power generation device. The gas diffusion layer (GDL) is one of the key components of the fuel cell. Its main functions are: transmitting electrons, transmitting reaction gases, draining water, transferring heat, and supporting the proton exchange membrane and catalyst layer.
[0003] Generally, the gas diffusion layer consists of two parts: a base layer and a microporous layer. The base layer is generally made of loose and porous carbon paper or carbon cloth after hydrophobic treatment. The traditional microporous layer is generally composed of carbon black and hydrophobic resin. Its main function is to reduce the contact resistance between the base layer and the catalyst layer, improve the pore structure of the base layer, and transmit water vapor. With the development and maturity of PEMFC technology, the requirements for the water management ability of GDL are getting higher and higher. That is, when operating at a large current density, the water generated by the reaction must be discharged in time to prevent the battery from being flooded. When operating at a small current density, it must have a certain water retention capacity to prevent the increase of membrane water loss impedance. To meet the water management ability of GDL, the microporous layer (MPL) is usually designed with a characteristic pore structure, and the MPL is a super-hydrophobic structure as a whole. In addition, in order to meet the life requirements of the stack operation, GDL is given more responsibilities, such as adding free radical scavengers to MPL to alleviate the attack of free radicals on the membrane, and adding metal ion scavengers to prevent the metal ions input from the outside or generated during the operation of the stack from poisoning the proton membrane or resin.
[0004] Patent CN117039011A discloses a composite microporous layer and its preparation method, and a proton exchange membrane fuel cell. The invention first prepares a hydrophobic microporous layer on the surface of the catalyst layer to reduce the resistance between the diffusion layer and the catalyst layer and increase the drainage; then prepares a hydrophilic microporous layer on the surface of the hydrophobic microporous layer, and prepares a conductive and gas-conductive leveling layer by gradient micropore distribution to improve the distribution of gas and water. However, since the catalyst layer cannot withstand high temperatures, it is difficult for the hydrophobic agent in the hydrophobic microporous layer to form a hydrophobic network through high-temperature treatment, forming a super-hydrophobic structure, which affects the drainage of the membrane electrode.
[0005] Patent CN112133931A discloses a "method for preparing a double-layer microporous layer of a gas diffusion layer of a proton exchange membrane fuel cell". In order to manufacture the double-layer microporous layer, too much organic solvent and costly nanomaterials are added to the slurry, which will seriously affect the pore structure and production cost of the gas diffusion layer.
[0006] Patent CN117117214A discloses a preparation method and gas diffusion layer of a fuel cell, which realizes the free radical capture function by adding a free radical scavenger and a perfluorosulfonic acid polymer to the catalyst layer slurry and drying the microporous layer under low temperature conditions. However, the hydrophobic agent in this method cannot achieve super hydrophobic function without high temperature treatment, so it is difficult for the microporous layer of the gas diffusion layer prepared by the invention to take into account both water management and free radical capture functions. Summary of the invention
[0007] The purpose of the present invention is to provide a double-layer microporous structure of a gas diffusion layer and a preparation method thereof, which has the characteristics of efficient water management and metal ion capture function.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A double-layer microporous structure of a gas diffusion layer, the gas diffusion layer comprising a base layer, a hydrophobic microporous layer, and a hydrophilic microporous layer which are stacked in sequence; wherein the base layer is prepared by hydrophobic treatment of carbon paper / carbon cloth with a hydrophobic agent, the hydrophobic microporous layer is prepared by coating, drying, and sintering a slurry composed of carbon powder, a hydrophobic agent, a solvent, and other additives, and the hydrophilic microporous layer is prepared by coating and drying a slurry composed of carbon powder, a polymer with a metal ion adsorption function, and a solvent.
[0010] A method for preparing a double-layer microporous structure of a gas diffusion layer comprises the following steps:
[0011] S1, soaking carbon paper or carbon cloth in a hydrophobic agent for 5 to 10 minutes, taking out and drying the carbon paper or carbon cloth in an oven at 80 to 120° C. for 5 to 20 minutes, and then sintering at 340 to 380° C. for 20 to 40 minutes to obtain a hydrophobic base layer;
[0012] S2, preliminarily mix and stir carbon powder, hydrophobic agent, solvent, and other additives (dispersant, thickener, leveling agent, pore former, free radical scavenger) in a ratio of 1:0.5:5:0.1-1:0.1:10:0.01 until there is no dry powder, put it into a high-speed shearing machine and stir it at a speed of 1000r / min for 30min to prepare a hydrophobic microporous layer slurry;
[0013] S3, coating the hydrophobic microporous layer slurry on the surface of the hydrophobic base layer by knife coating, drying in an oven at 80-120°C for 5-20 min, and sintering at 340-380°C for 20-40 min to prepare a hydrophobic microporous layer, and controlling the hydrophobic microporous layer loading to 0.5-2 mg / cm 2 ;
[0014] S4, preliminarily stirring and mixing the carbon powder, the polymer with metal ion adsorption function, and the solvent in a ratio of 0:2:5 to 1:0.5:20 until there is no dry powder, and putting them into a shearing machine and stirring them at a speed of 1000r / min for 30min to prepare a hydrophilic microporous layer slurry (wherein the ratio of carbon powder can be 0, that is, only the polymer with metal ion adsorption function and the solvent are configured into a slurry in a ratio of 2:5 to 0.5:20 for subsequent steps);
[0015] S5, coating the hydrophilic microporous layer slurry on the surface of the hydrophobic microporous layer by spraying, with a spraying distance of 80 mm and a spraying rate of 60 mm / s. After coating, drying is performed at 80-120°C for 10-40 min to obtain a hydrophilic microporous layer, and the hydrophilic microporous layer loading is controlled to be 0.1-1 mg / cm 2 .
[0016] As a preferred technical solution of the present invention, in step S1, the hydrophobic agent in the substrate treatment process is a polytetrafluoroethylene solution or a polyvinylidene fluoride solution with a mass fraction of 5 to 10 wt.%.
[0017] As a preferred technical solution of the present invention, in steps S2 and S4, the carbon powder in the hydrophobic microporous layer and the hydrophilic microporous layer is one or more of carbon black, acetylene black, carbon nanotubes, graphene, and carbon fiber.
[0018] As a preferred technical solution of the present invention, in steps S2 and S4, the solvents in the hydrophobic microporous layer and the hydrophilic microporous layer are one or more of ethanol, ethylene glycol, isopropanol, and n-propanol.
[0019] As a preferred technical solution of the present invention, it is characterized in that the solvent used in the preparation of the hydrophobic microporous layer and the hydrophilic microporous layer is one or more of ethanol, ethylene glycol, isopropanol, n-propanol and water.
[0020] As a preferred technical solution of the present invention, in step S2, the preparation of the hydrophobic microporous layer slurry includes an additive, wherein the additive is one of a dispersant, a pore-forming agent, and a free radical scavenger, the dispersant is one of methyl cellulose, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate, the pore-forming agent is one of ammonium carbonate and ammonium bicarbonate, and the free radical scavenger is one of cerium oxide and manganese oxide.
[0021] As a preferred technical solution of the present invention, the polymer with metal ion adsorption function in step S4 is one of perfluorosulfonic acid polymer (Nafion), non-fluorocarbon hydrogen sulfonic acid resin (sulfonated polyetheretherketone (SPEEK), sulfonated polyetherketone (SPEK), sulfonated polybenzimidazole (SPBI)).
[0022] Beneficial effects of the present invention:
[0023] (1) The double-layer microporous structure designed by the present invention, wherein the super-hydrophobic macroporous structure of the hydrophobic microporous layer ensures excellent drainage capacity when the proton exchange membrane fuel cell is running at a high current density, and the hydrophilic microporous layer enhances the contact area with the catalyst layer and reduces the contact resistance, thereby improving the adsorption of the electrode and the performance of the low-current density area in the proton exchange membrane fuel cell. At the same time, the hydrophilic microporous layer has the structural characteristics of both the catalyst layer and the microporous layer, reducing the hydrophobic gradient and pore gradient from the catalyst layer to the gas diffusion layer, and plays a transition role;
[0024] (2) A polymer with metal adsorption capacity is added to the hydrophilic microporous layer. The acid ions (such as sulfonate ions) in the polymer used in the present invention will interact electrostatically or coordinate with the metal ions, thereby attracting or forming coordination bonds with the positively charged metal ions, thereby firmly binding the metal ions. At the same time, the polymer polymer chains also form certain channels or gaps in space, which can accommodate metal ions and stably adsorb them through the interaction between molecular chains; therefore, the hydrophilic microporous layer plays a barrier role in preventing metal ion contamination in the membrane electrode. Due to the metal ion adsorption function of the polymer in the hydrophilic layer, it can adsorb metal ions (Cu ions) introduced from the outside air or generated during the operation of the battery stack. 2+ , Fe 3+ 、Ce 3+ etc.), reducing the extent to which these metal ions enter the catalytic layer and destroy the three-phase reaction interface when the fuel cell stack is running. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0026] Figure 1 is a schematic diagram of a double-layer microstructure of a gas diffusion layer prepared by the present invention;
[0027] Figure 2 Polarization curves of the gas diffusion layers prepared in the examples and comparative examples after being assembled into membrane electrodes. DETAILED DESCRIPTION
[0028] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0029] Example 1
[0030] S1, soaking the carbon paper in a polytetrafluoroethylene emulsion with a mass fraction of 5wt.% for 10 minutes, taking it out and drying it in an oven at 80°C for 5 minutes, and then sintering it at 340°C for 20 minutes to obtain a hydrophobic base layer;
[0031] S2, 1g of carbon black, 3g of 10wt.% polytetrafluoroethylene emulsion, 7g of ethanol, and 0.1g of ammonium carbonate were mixed until there was no dry powder, and the mixture was placed in a high-speed shearing machine and stirred at a speed of 1000r / min for 30min to prepare a hydrophobic microporous layer slurry;
[0032] S3, coating the hydrophobic microporous layer slurry on the surface of the hydrophobic base layer by knife coating, drying in an oven at 80°C for 5 minutes, and sintering at 340°C for 20 minutes to prepare a hydrophobic microporous layer, and controlling the hydrophobic microporous layer loading to 1.5 mg / cm 2 ;
[0033] S4, 1g of carbon powder, 5g of 20wt.% perfluorosulfonic acid resin D2020, and 5g of water were preliminarily mixed until there was no dry powder, and stirred at a speed of 1000r / min for 30min to prepare a hydrophilic microporous layer slurry;
[0034] S5, coating the hydrophilic microporous layer slurry on the surface of the hydrophobic microporous layer, drying at 80°C for 20 min to obtain a hydrophilic microporous layer, and controlling the hydrophilic microporous layer loading to 0.5 mg / cm 2 .
[0035] Example 2
[0036] S1, soaking the carbon paper in a polytetrafluoroethylene emulsion with a mass fraction of 10wt.% for 5 minutes, taking it out and drying it in an oven at 80°C for 5 minutes, and then sintering it at 340°C for 20 minutes to obtain a hydrophobic base layer;
[0037] S2, 1g of carbon powder, 3g of 10wt.% polytetrafluoroethylene emulsion, 5g of ethanol, 4g of water, and 0.01g of cerium oxide were preliminarily mixed until there was no dry powder, put into a high-speed shearing machine, and stirred at a speed of 1000r / min for 30min to prepare a hydrophobic microporous layer slurry;
[0038] S3, coating the hydrophobic microporous layer slurry on the surface of the hydrophobic base layer by knife coating, drying in an oven at 80°C for 5 minutes, and sintering at 340°C for 20 minutes to prepare a hydrophobic microporous layer, and controlling the hydrophobic microporous layer loading to 2 mg / cm 2 ;
[0039] S4, 1g of 20wt.% perfluorosulfonic acid resin D2020, 5g of water and 5g of ethanol were stirred at a speed of 1000r / min for 30min to prepare a hydrophilic microporous layer slurry;
[0040] S5, coating the hydrophilic microporous layer slurry on the surface of the hydrophobic microporous layer, drying at 80°C for 20 min to obtain a hydrophilic microporous layer, and controlling the hydrophilic microporous layer loading to 0.1 mg / cm 2 .
[0041] Example 3
[0042] S1, soaking the carbon paper in a polytetrafluoroethylene emulsion with a mass fraction of 5wt.% for 10 minutes, taking it out and drying it in an oven at 80°C for 5 minutes, and then sintering it at 340°C for 20 minutes to obtain a hydrophobic base layer;
[0043] S2, 1g of carbon powder, 3g of 10wt.% polytetrafluoroethylene emulsion, 4g of ethanol, 4g of water, and 0.1g of methyl cellulose were preliminarily mixed until there was no dry powder, and stirred at a speed of 1000r / min for 30min to prepare a hydrophobic microporous layer slurry;
[0044] S3, coating the hydrophobic microporous layer slurry on the surface of the hydrophobic base layer by knife coating, drying in an oven at 80°C for 5 minutes, and sintering at 340°C for 20 minutes to prepare a hydrophobic microporous layer, and controlling the hydrophobic microporous layer loading to 1.5 mg / cm 2 ;
[0045] S4, 1g of carbon black, 5g of sulfonated polybenzimidazole (SPBI, a non-fluorinated hydrogen sulfonic acid polymer) with a mass fraction of 20wt.%, 5g of ethanol, and 5g of water were fully stirred at a speed of 1000r / min for 30min to prepare a hydrophilic microporous layer slurry;
[0046] S5, coating the hydrophilic microporous layer slurry on the surface of the hydrophobic microporous layer, drying at 80°C for 20 min to obtain a hydrophilic microporous layer, and controlling the hydrophilic microporous layer loading to 0.5 mg / cm 2 .
[0047] Comparative Example 1
[0048] According to the preparation method of the gas diffusion layer with ion adsorption function described in the existing invention patent:
[0049] The carbon paper was soaked in a polytetrafluoroethylene emulsion with a mass fraction of 5 wt.% for 0.5 h, dried at 80°C for 5 min, and sintered at 340°C for 20 min to obtain a hydrophobic base layer;
[0050] 10 parts of carbon black, 10 parts of polytetrafluoroethylene emulsion with a mass fraction of 20 wt.%, 10 parts of perfluorosulfonic acid resin D2020 with a mass fraction of 20 wt.%, 50 parts of ethanol, and 50 parts of water were fully stirred at a speed of 300 r / min for 2 hours to prepare a microporous layer slurry;
[0051] The slurry was sprayed on the surface of the hydrophobic substrate by ultrasonic spraying until the loading was 2 mg / cm 2 , and dried at 80°C to obtain a gas diffusion layer with ion adsorption function.
[0052] The gas diffusion layers prepared in Examples 1-3 and the comparative example were made into membrane electrodes, respectively, and performance tests were performed, with the membrane electrode configuration being the same. The results are shown in the attached figure. Figure 2 As shown, compared with Comparative Example 1, the method described in the embodiment has better drainage ability and higher large electrical density performance.
[0053] When the present invention is used:
[0054] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A double-layer microporous structure of a gas diffusion layer, characterized in that: The gas diffusion layer comprises a base layer, a hydrophobic microporous layer and a hydrophilic microporous layer which are stacked in sequence; wherein the base layer is prepared by hydrophobic treatment of carbon paper, the hydrophobic microporous layer is prepared by coating, drying and sintering a slurry composed of carbon powder, a hydrophobic agent, a solvent and other additives, and the hydrophilic microporous layer is prepared by coating and drying a slurry composed of carbon powder, a polymer with metal ion adsorption function and a solvent.
2. The double-layer microporous structure of the gas diffusion layer according to claim 1, characterized in that: The hydrophobic agent is a polytetrafluoroethylene solution or a polyvinylidene fluoride solution with a mass fraction of 5 to 10 wt.%.
3. The double-layer microporous structure of the gas diffusion layer according to claim 1, characterized in that: The carbon powder in the hydrophobic microporous layer and the hydrophilic microporous layer is one or more of carbon black, acetylene black, carbon nanotubes, graphene, and carbon fiber.
4. The double-layer microporous structure of the gas diffusion layer according to claim 1, characterized in that: The solvents in the hydrophobic microporous layer and the hydrophilic microporous layer are one or more of ethanol, ethylene glycol, isopropanol and n-propanol.
5. The double-layer microporous structure of the gas diffusion layer according to claim 1, characterized in that: The polymer with metal ion adsorption function is one of perfluorosulfonic acid polymer (Nafion), non-fluorocarbon hydrogen sulfonic acid resin (sulfonated polyetheretherketone (SPEEK), sulfonated polyetherketone (SPEK), sulfonated polybenzimidazole (SPBI)).
6. A method for preparing a double-layer microporous structure of a gas diffusion layer according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, carbon paper or carbon cloth is soaked in a hydrophobic agent, dried at 80-120°C for 5-20min, and sintered at 340-380°C for 20-40min to obtain a hydrophobic base layer; S2, carbon powder, hydrophobic agent, solvent, other additives (dispersant, thickener, leveling agent, pore-forming agent, free radical scavenger) are mixed in a ratio of 1:0.5:5:0.1-1:0.1: The ratio of 10:0.01 is fully stirred to form a hydrophobic microporous layer slurry; S3, applying the hydrophobic microporous layer slurry on the surface of the hydrophobic base layer by screen printing, spraying, blade coating, etc., drying at 80-120°C for 5-20 min, and drying at 340-380°C for 20-40 min to obtain a hydrophobic microporous layer, and controlling the hydrophobic microporous layer loading to be 0.5-2 mg / cm 2 ; S4, fully mixing carbon powder, polymer with metal ion adsorption function, and solvent in a ratio of 0:2:5 to 1:0.5:20 to prepare a hydrophilic microporous layer slurry (wherein the ratio of carbon powder can be 0, that is, only the polymer with metal ion adsorption function and the solvent are configured into a slurry in a ratio of 2:5 to 0.5:20 for subsequent steps); S5, applying the hydrophilic microporous layer slurry on the surface of the hydrophobic microporous layer by screen printing, spraying, blade coating, etc., drying at 80-120°C for 10-40 minutes to obtain a hydrophilic microporous layer, and controlling the hydrophilic microporous layer loading to be 0.1-1 mg / cm 2 .
7. According to claim 6, the double-layer microporous structure of the gas diffusion layer described in S2 is characterized in that The additive is one of a dispersant, a pore-forming agent, and a free radical scavenger; the dispersant is one of methyl cellulose, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; the pore-forming agent is one of ammonium carbonate and ammonium bicarbonate; and the free radical scavenger is one of cerium oxide and manganese oxide.
Citation Information
Patent Citations
Preparation method of double microporous layer of gas diffusion layer of proton exchange membrane fuel cell
CN112133931A
Preparation method of gas diffusion layer of fuel cell and gas diffusion layer
CN117117214A
Gas diffusion layer for fuel cell and preparation method and application thereof
CN111029605A
Fuel cell microporous layer and preparation method thereof
CN118867272A
Membrane electrode assembly for fuel cells and fabrication method thereof
US20070134545A1
Cited By
Integrated fuel cell membrane electrode and preparation method thereof
CN121307109A
Double-layer microporous layer for fuel cell, preparation method of double-layer microporous layer, gas diffusion layer and fuel cell
CN121583941A